Modulation of intestinal inflammation by dietary polyphenols in comparison with 5-aminosalicylic acid: an in vitro approach - Serra, Diana Jurado Santos (2016)
Tese de doutoramento em Ciências Farmacêuticas, no ramo de Bioquímica, apresentada à Faculdade de Farmácia da Universidade de Coimbra